Integrating Outdoor Education in Multicultural Settings: Perspectives from Italian Primary Schools - Natalini, Alessandra (Current Progress in Arts and Social Studies Research Vol. 2, 2024)
The present research aims to understand the opinions of teachers, parents and primary school children about Outdoor Education (OE) and its use in schools, as well as the intrinsic characteristics that distinguish its effectiveness in terms of inclusion processes for children with Migratory Background (MB). Grounded the examination of the dimensions and variables present in the studies analysed allows us to detect how the variety of individual and socio-cultural factors requires knowledge on the part of the teachers of the background of each student and the use of flexible approaches, active methodologies and operational techniques, which look at forms of cooperative and participatory learning, useful to correspond to the needs of children and those with an MB. Grounded Theory (GT) requires a constant comparison at every level of analysis (between data, between data and categories, between categories, between observed events and categories, between category properties, etc.) and their simultaneous collection and analysis. In addition, the researcher can make use of the production of diagrams, which have the function of scaffolding that facilitates the comparison between categories, and of memos, which constitute the annotations on the research process, a metacognitive space, of reflection on the data collection in which to make explicit the choices made, which help him to make his point of view explicit. The research has made it possible to obtain useful data on how the OE educational approach is currently adopted within the Italian context and how this can contribute to the process of inclusion of children with a migrant background, which can be said to be complex problems and still felt by teachers of all levels. Future studies could envisage replicative forms of the present research on territorial contexts different from those involved, both in Italy and abroad, such as in countries that already implement it in multicultural school contexts or where the tradition of OE appears more consolidated, as in the case of Northern European countries. In a first analysis, opinions of the interviewees, the OE would seem to help overcome the main obstacles that students with BM encounter at school in terms of achieving training objectives, through versatile and inclusive OE methodologies, attributable to forms of laboratory and experiential and group teaching, which focus on the observation of concrete examples taken from the environment. The EO would also seem to facilitate concrete cultural experiences and positive inter-ethnic relations.